Avaliação do desenvolvimento de crianças matriculadas em uma creche conveniada do município de São Paulo - Merino, Paola Mendez [UNIFESP] (2017)
Objectives: General: To evaluate the neuropsychomotor development of children from 0 to 60 months of age attending Cruz de Malta’s day care center. Specifics: To characterize the neuropsychomotor development of children using the test Denver II, to describe sociodemographic, neonatal, family and institutional characteristics of the studied children and to relate the sociodemographic, neonatal, family and institutional variables with the neuropsychomotor development of the children. Methods: Descriptive, cross-sectional study, approved by the Research Ethics Committee of UNIFESP n°. 1,575,822/16. The sample consisted of 152 children, and those with health problems that prevented participation in the study activities were excluded. Two instruments collected data, one related to sociodemographic, neonatal, family and institutional variables of the children, and the other to the evaluation of child development, by the Denver II Development Screening Test. Descriptive and bivariate statistics were used to analyze the data. Results: The majority of the children were younger than 36 months old (67.7%) and female (50.7%); 95.4% of the mothers got prenatal care; 53.8% of the children were born in normal labor, with a mean gestational age of 38.4 weeks, Apgar at the 5th minute of 9.4 and birth weight of 3.144g; 9.2% of them were underweight, 1.3% were very underweight and 11.3% were premature; 24% of the children presented neonatal complications, being the most frequent ones: jaundice, prematurity and low birth weight; 32% had previous hospitalizations, respiratory problems being the main reason; 65.1% of the children were eutrophic and 25.7% were at risk of overweight; 16.9% of the children had anemia; 98% of them were breastfed, and 68.4% of them received exclusive breastfeeding in a mean of 101.7 days; the majority of the parents lived together, being 19.1% married and 38.8% in a stable union; 50.3% of mothers were aged between 19 and 29 years; the most frequent age groups of the parents were 19 to 29 years and 29 to 39 years corresponding to 41.8% each; 37% of mothers and 37.6% of parents had completed high school; 61.6% and 90.1% respectively were employed; 55.3% of families had a family income of one minimum wage. As to the permanence of the child in the day care center, the average age of admission to the institution was 15.4 months, and their time of attendance at the institution was, on average, 13.8 months; evaluated by Denver II test, 73.7% of the children had the result "Normal" and 26.3% "Questionable"; 118 items identified as "Caution", 68% were in the Language area, presented by 63 (41.4%) of the children; of the 40 items with "Delay", 87.5% were from the Language area, present in 13.2% of the children; some have presented more than one "delay/caution" item by area and/or in more than one area. There was a statistically significant association between the Denver II score and the current age of the children (p <0.001), Hb level (p = 0.030), mothers' work status (p = 0.005) and frequency of child day care center (p = 0.001). Conclusion: Most of the children evaluated presented the results of the test Denver II "Normal", with more “caution” in the area of language. Final considerations: It is important to emphasize the importance of periodic evaluation of the development of the children who attend this educational equipment, in this and other institutions.